Living letters of the law: ideas of the Jew in medieval Christianity - Cohen, Jeremy (The S. Mark Taper Foundation imprint in Jewish studies, 1999)
In Living Letters of the Law, Jeremy Cohen investigates the images of Jews and Judaism in the works of medieval Christian theologians from Augustine to Thomas Aquinas. He reveals how-and why-medieval Christianity fashioned a Jew on the basis of its reading of the Bible, and how this hermeneutically crafted Jew assumed distinctive character and power in Christian thought and culture.Augustine's doctrine of Jewish witness, which constructed the Jews so as to mandate their survival in a properly ordered Christian world, is the starting point for this illuminating study